MRI Evaluation of Cervical Carcinoma Stage II at a Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Diagnosis of clinical staging is very crucial for the management of cervical carcinoma.Objective: The purpose of the present study was to evaluate the MRI and clinical staging of IIA and IIB cervical carcinoma.Methodology: This cross-sectional study was conducted in Department of Radiology & Imaging at Dhaka Medical College Hospital, Dhaka, Bangladesh with the collaboration of Obstetrics and Gynecology unit as well as the Department of Pathology of Dhaka Medical College, Dhaka, Bangladesh from July 2010 to June 2012 for a period of two years. All patients with MRI examination who had given the written permission for the use of their data for research purposes at the time of their scan were selected as study population. The cervix and vagina were visually inspected for superficial evidence of the extent of tumor. Biopsied were not routinely performed since patients were usually referred only after a biopsy and had confirmed the diagnosis of invasive carcinoma. Assessments of the extent of tumor, parametrial extension, lymph nodes were evaluated. Then the findings of MRI clinical examination, surgical findings and histopathological reports were recorded on a preformed data sheet. Finally, the diagnostic effectiveness of MRI staging and clinical FIGO staging were evaluated against the surgico-histopathological reports.Result: A total number of 30 patients were recruited for this study. The mean age with SD of the study population were 57.82±13.34 years. The sensitivity, specificity, PPV, NPV and accuracy of MRI of the detection of IIA of cervical carcinoma was 80.0%, 100.0%, 100.0%, 90.9% and 93.33% respectively. However, the sensitivity, specificity, PPV, NPV and accuracy of clinical examination of the detection of IIA of cervical carcinoma was 84.34%, 63.86%, 84.87%, 45.86% and 67.44% respectively.Conclusion: In conclusion the diagnostic validity of MRI for the detection of carcinoma cervix stage IIA is better than clinical examination.Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 113-117